2023
DOI: 10.3390/life13071539
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salinity, Mangrove Community Ecology, and Organic Blue Carbon Stock in Response to Cyclones at Indian Sundarbans

Abstract: Climate change-induced frequent cyclones are pumping saline seawater into the Sundarbans. Fani, Amphan, Bulbul, and Yaas were the major cyclones that hit the region during 2019–2021. This study represents the changes in the soil parameters, mangrove biodiversity and zonation due to the cyclone surges in the Indian Sundarbans between 2017 and 2021. Increasing tidal water salinity (parts per thousand) trends in both pre-monsoon (21 to 33) and post-monsoon (14 to 19) seasons have been observed between 2017 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Indian Sundarbans in the phytosociological study had five zones but presently transformed into four zones (loss of a few species of mangroves). It is due to the impact of Tides (Low and High), Regional Sea level changes (RSLR), the impact of cyclones and human interventions, between 2017-2021(Chowdhury et al, 2023 [45]). The south 24 Parganas is disaster-wise very sensitive.…”
Section: Ganga-brahmaputra Meghana (Gbm) Deltamentioning
confidence: 99%
“…Indian Sundarbans in the phytosociological study had five zones but presently transformed into four zones (loss of a few species of mangroves). It is due to the impact of Tides (Low and High), Regional Sea level changes (RSLR), the impact of cyclones and human interventions, between 2017-2021(Chowdhury et al, 2023 [45]). The south 24 Parganas is disaster-wise very sensitive.…”
Section: Ganga-brahmaputra Meghana (Gbm) Deltamentioning
confidence: 99%
“…Not only anthropogenic activities affect mangroves in relation to carbon sequestration, but also climate change with strong cyclones that flood the coasts of these ecosystems with high concentrations of salt, altering soil conditions. Chowdhury et al [18] found, in the mangroves of Sundarbans, India, between 2017 and 2021, that an increase in salinity by 31% can reduce the organic carbon stored in the soil by up to 46%, as well as reducing available phosphorus and available nitrogen by 33% and 30%, respectively. Some sensitive mangroves have disappeared with these saline concentrations, so the actions of climate change must be counteracted so as not to affect these carbon sinks.…”
Section: Introductionmentioning
confidence: 99%